Halebü'ş-Şehbâ' fî 'uyûni'ş-şuarâ - 880-01 Kujjah, Hasan. (Leiden ; Boston)
5 cilt (1. c. [3], 815, xxi sayfa ; 2. c. [3], 848, xxxiii sayfa ; 3. c. [3], 930, xx sayfa ; 4. c. [3], 345, ix sayfa ; 5. c. [3], 482, ix sayfa)
Keywords: “Aleppo in Classical Poetry sheds light Aleppo by collecting and indexing more than 900 poems that have been written about the city or mentioned it, from the 7th century to the early 20th century. The poems reflect the various civilizational aspects of Aleppo, an authentic and cosmopolitan city, the oldest functional in the world, and one of the richest in terms of culture and heritage. The authors, Hasan Kujjah and Mohammad Kujjah, aim to investigate the actual and symbolic value of Aleppo through poets' eyes, emphasizing the contribution that poetry made to revealing the history of Arab and Islamic cities and their values, both its tangible and emotional dimensions“ --